The role of speech therapist in the educational inclusion of the schoolchildrens with disorders of the oral communication - Murguia Moré, Merling; Hernández Nodarse, Tania; Carrera Morales, Mercedes Alipia (Avances en Supervisión Educativa, 2016)
Today the educational attention to people with special educational necessities assumes a position around the educational inclusion. In this article are analyzed the studies published on the topic.. The gathered information and the empiric evidences give bill of the transformations that should be operated in the work of the speech therapist to adapt to this reality and to optimize the attention to the scholars with disorders of the oral communication. Therefore, the objective of the article is to propose how redimensionar the role of the speech therapist to contribute to the educational inclusion of schoolchildrens of the Primary Education with disorders of the oral communication.
Keywords: speech therapist; educational inclusion; schoolchildrens; disorders; oral communication